2001
DOI: 10.1016/s0090-4295(00)01060-8
|View full text |Cite
|
Sign up to set email alerts
|

Five-year retrospective, multi-institutional pooled analysis of cancer-related outcomes after cryosurgical ablation of the prostate

Abstract: Objectives. To define the potential role of cryosurgical ablation of the prostate (CSAP) as a treatment option for patients with localized prostate carcinoma (PCA), we performed a retrospective outcomes analysis of a large database of patients undergoing CSAP constructed from five institutions and compared this with matching outcomes from contemporary reports of patient outcomes after radiotherapy. Methods. A total of 975 patients who underwent CSAP as primary therapy from January 1993 to January 1998 with suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
1
17

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(123 citation statements)
references
References 30 publications
4
101
1
17
Order By: Relevance
“…12,22 CRYO outcomes are similarly unclear and have been reported many ways, including threshold criteria and the first ASTRO definition. [7][8][9] Currently, there is no universally agreed upon definition of …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,22 CRYO outcomes are similarly unclear and have been reported many ways, including threshold criteria and the first ASTRO definition. [7][8][9] Currently, there is no universally agreed upon definition of …”
Section: Discussionmentioning
confidence: 99%
“…7,8 We previously reported a phase 2 CRYO series with 5-year probabilities of maintaining a prostate-specific antigen (PSA) level 1.0 ng/mL for low-risk, intermediate-risk, and high-risk patients of 75%, 89%, and 76%, respectively. 9 Herein, we present the results of our singleinstitution, randomized trial in which we compared EBRT with CRYO for clinically localized prostate cancer at the Tom Baker Cancer Center.…”
mentioning
confidence: 99%
“…The patients with medium risk had a 67% biochemical freedom of disease, and for high-risk patients it was 41%. These results are encouraging and place cryotherapy between radical prostatectomy and radiotherapy (EBRT and BT) in effectiveness [12].…”
Section: Results Of Modern Cryosurgery For Prostate Cancermentioning
confidence: 89%
“…Originally accepted primarily for salvage after local failure of radiation therapy, cryoablation is now used increasingly often as a primary treatment. Results from several large studies have showed that cryoablation of the prostate provides a long-term, durable response with regard to disease control [16]. Recent advances in technology for cryoablation have also produced significant decreases in associated complications and morbidity.…”
Section: Discussionmentioning
confidence: 99%